2015
DOI: 10.1017/s0007114515000914
|View full text |Cite
|
Sign up to set email alerts
|

A combination of probiotics and whey proteins enhances anti-obesity effects of calcium and dairy products during nutritional energy restriction in aP2-agouti transgenic mice

Abstract: Lactobacillus rhamnosus GG, Lactobacillus paracasei TMC0409, Streptococcus thermophilus TMC1543 and whey proteins were used to prepare fermented milk. For the experiment aP2 -agouti transgenic mice were pre-treated with a high-sucrose/high-fat diet for 6 weeks to induce obesity. The obese mice were fed a diet containing 1·2 % Ca and either non-fat dried milk (NFDM) or probiotic-fermented milk (PFM) with nutritional energy restriction for 6 weeks. The animals were examined after the treatment for changes in bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Recent studies highlighted that some bacterial strains, such as Lactobacillus spp. and Bifidobacterium spp., play a role in energy metabolism and weight management in obese rats and humans ( 21 23 ). Identifying which bacterial strain should be used as a probiotic supplement is extremely important because it has been suggested that the health-promoting properties of probiotics are strain-dependent ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlighted that some bacterial strains, such as Lactobacillus spp. and Bifidobacterium spp., play a role in energy metabolism and weight management in obese rats and humans ( 21 23 ). Identifying which bacterial strain should be used as a probiotic supplement is extremely important because it has been suggested that the health-promoting properties of probiotics are strain-dependent ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant suppression of the adipose tissue gene expression of 11ß-hydroxysteroid dehydrogenase. Stimulating significant up regulation of skeletal muscle and causing significant decrease in the plasma concentration of insulin, malondialdehyde, TNF-α, monocyte, chemodactic protein-1 and C-reactive protein.[32] Streptococcus thermophilus TMC1543 Lactobacillus paracasei subsp. paracasei NTU 101 (W101)Vegetable productDecrease in formation of lipid plaques in the aorta, reduced the adipocyte cross-sectional area and diameter, and reduced the levels of CCAAT/enhancer-binding protein β (C/EBPβ), peroxisome proliferator associated receptor γ (PPARγ), and C/EBPα.…”
Section: Probiotic Lab and Obesity Treatmentmentioning
confidence: 99%
“…Human studies have shown that dietary calcium intake is inversely associated with body weight, body fat or body mass index and although weight loss is sometimes not dramatic, it would be considered significant at a population level . Transgenic animal models (with an overexpression of the agouti gene in adipocytes) have helped in the elucidation of the potential mechanism of calcium in these particular cells . Overall, it is suggested that this nutrient (sometimes in conjunction with vitamin D) increases faecal energy loss and leads to a less positive energy balance .…”
Section: Introductionmentioning
confidence: 99%